LITERATURE AS A MIRROR OF THE PSYCHE: A FREUDIAN PSYCHOANALYTIC APPROACH TO COLONIAL TRAUMA IN INDIAN HORSE - Mr. Zafar Ali; Ms. Aroona Saleem Jan; Dr. Muhammad Ilyas (International Journal of Contemporary Issues in Social Sciences, 2024)
This research focuses on the application of Freudian psychoanalysis to Richard Wagamese’s novel Indian Horse, highlighting the psychological development and inner conflicts of the main character, Saul Indian Horse. The study analyzes how Freudian concepts such as repression, trauma, and the tripartite structure of the psyche (id, ego, superego) manifest in the experience and behavior of Saul. The main objective of the paper is to presents how the trauma of the St. Jerome’s Indian Residential School system and the loss of cultural identity affect the psyche of the main character. By analyzing Saul’s journey, the study intends to the show the deeper psychological issues and the impact of colonial trauma on Indigenous identity and mental health. The study also aims to contribute to the understanding of how literature mirrors the complex psychological issues and the ways in which historical and cultural trauma can shape an individual’s psyche. The study is qualitative in nature the interprets the story of the novel according to the theoretical views of Sigmund Freud. The results exhibit that Saul experienced psychological trauma and mental conflicts due to his past intolerable experiences at his school that highlight the psychological effects of colonialism.